2022
DOI: 10.1371/journal.pone.0278038
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic impact of lymph node dissection for clinically node-negative upper urinary tract urothelial carcinoma in patients who are treated with radical nephroureterectomy

Abstract: Background To evaluate the prognostic impact of lymph node dissection (LND) in patients who underwent radical nephroureterectomy (RNU) with bladder cuff excision (BCE) for clinically node-negative (cN0) upper urinary tract urothelial carcinoma (UTUC). Methods We retrospectively enrolled 520 patients with cN0 UTUC in a single tertiary referral center from 2000 to 2015. The patients were divided into three groups: patients with and without pathologically proved lymph node metastasis (pN1–3 and pN0, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…On the other hand, some retrospective studies showed that there was no survival difference between cN0 patients who did and did not undergo LND, but the subgroup analyses according to the number of removed LNs were not performed [ 19 , 20 ]. One of the multicenter retrospective analyses demonstrated that in cN0 muscle-invasive UTUC (≥pT2 stage) LND did not provide a survival benefit when compared to no LND [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some retrospective studies showed that there was no survival difference between cN0 patients who did and did not undergo LND, but the subgroup analyses according to the number of removed LNs were not performed [ 19 , 20 ]. One of the multicenter retrospective analyses demonstrated that in cN0 muscle-invasive UTUC (≥pT2 stage) LND did not provide a survival benefit when compared to no LND [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, the pNx cohort includes both pN0 and pN+ patients if they had undergone LND; therefore, when compared with pN0 patients, worse oncologic outcomes in pNx patients (no LND) would be expected. On the contrary, Burger et al , Li et al , Hsieh et al , Lughezzani et al , Chappidi et al , and Lenis et al showed no differences in DFS, CSS, and OS between patients with pNx and pN0, suggesting that survival outcomes are affected by patient selection, as patients harboring advanced disease associated with potential lymph node metastasis being more likely to undergo LND [28,31,32,35,37,38].…”
Section: Evidence Synthesismentioning
confidence: 98%
“…The authors showed inferior DFS (hazard ratio 2.40, P < 0.001) and CSS (hazard ratio 2.39, P < 0.001) in pN+ patients compared with pN0 patients using multivariable Cox regression analysis [27]. As shown in Table 1, compared with pN0, the negative prognostic impact of pN+ with regard to DFS and CSS has been supported by several studies, such as Burger et al [28] in 2011 (hazard ratio for DFS: 2.0, hazard ratio for CSS: 2.1, n = 785), Mason et al [29] in 2012 (hazard ratio for DFS: 2.01, hazard ratio for CSS: 2.94, n = 1029), Ikeda et al in 2017 (hazard ratio for DFS: 3.25, hazard ratio for CSS: 3.56, n = 399) [30], Li et al in 2021 (hazard ratio for CSS: 3.08, hazard ratio for CSS: 4.41, n = 1340) [31], Hsieh et al [33] in 2022 (hazard ratio for CSS: 2.01, n = 520) [32], Lee et al [34 ▪▪ ] in 2022 ( P < 0.001 in DFS and P = 0.01 in CSS, n = 658), and Hakimi et al in 2022 (HR for DFS: 1.80, HR for CSS: 2.74, n = 877). In addition, two studies showed that pN+ was associated with worse OS in UTUC patients compared to pN0; for example, Mason et al in 2012 (HR for OS: 2.70, n = 1029) and Hakimi et al in 2022 (hazard ratio for OS: 2.77, n = 877) [29,31].…”
Section: Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations